Coping with Urban Fiscal Stress around the World - Dethier, Jean-Jacques (World Bank, Washington, DC, 2014)
The economic recession, the end of stimulus funding and central government cutbacks, rising social costs and aging, and the need for infrastructure upgrading for urbanization are putting enormous fiscal stress on cities. The financing capacity of municipalities is greatly affected because of the decline in the tax base, expenditure pressures, and growing and more expensive debt. Today's urban fiscal crisis is similar to that experienced in the 1970s, but the growing urbanization in the world and massive increase in municipal access to financial markets create a new context. This paper surveys three important topics related to the urban fiscal crisis in developed and developing countries: How do cities finance themselves? When they have access to financial markets, should city managers use loans, own revenues or private-public partnerships to pay for municipal expenditures? And what are the remedies to municipal fiscal crises in case of insolvency?